Factors Affecting Turnover Intention of Generation Y Workers in Timber (Wood Working) Industry of Malaysia - Tan, Hee Lun (2019)
Human labour is an important asset for all the industry, especially for manufacturing industry. In woodworking industry, human labour plays a significant role in the manufacturing process. However, this industry is facing shortage of workers and difficult to retain their existing employees. Hence, the researcher aim to find out the factors that affect the turnover intention of the Generation Y who are the major workforce in the current economy. Based on the literature review, the researcher has identified five factors that influence the turnover intention of Generation Y, namely personal dimensions, job attitudes, work-life balance, organizational strategies and working environment. The objectives of the study are to examine if the five factors have negative direct effect towards the turnover intention. As such, the researcher used simple random sampling to conduct a survey among the Generation Y workers in the woodworking industry. The results show that all factors have negative direct effect on employees’ turnover intention. However, only organizational strategies and working environment are the significant factors that influence the turnover intention of the Generation Y workers. This study can provide the top management of the woodworking industry to formulate better strategies to reduce their turnover intention and attract good employees. Nonetheless, the researcher has highlighted the limitation of the study and proposed few recommendations to improve future study.